MI5 in the Great War - Edited by West, Nigel (London Biteback Publishing, 2014)
In 1921, MI5 commissioned a comprehensive, top-secret review of the organisation's operations during the First World War. Never intended for circulation outside of the government, all seven volumes of this fascinating and unique document remained locked away in MI5's registry? until now. Recently declassified and published here for the first time, MI5 in the Great War is filled with detailed, and previously undisclosed, accounts centring on the Security Service's activities during the conflict.
Include Appendix
Keywords: Secret service -- World War (1914-1918) -- Great Britain -- Great Britain. MI5